Skip to main content

Robust Dickey–Fuller tests based on ranks for time series with additive outliers

Abstract

In this paper the unit root tests proposed by Dickey and Fuller (DF) and their rank counterpart suggested by Breitung and Gouriéroux (J Econom 81(1): 7–27, 1997) (BG) are analytically investigated under the presence of additive outlier (AO) contaminations. The results show that the limiting distribution of the former test is outlier dependent, while the latter one is outlier free. The finite sample size properties of these tests are also investigated under different scenarios of testing contaminated unit root processes. In the empirical study, the alternative DF rank test suggested in Granger and Hallman (J Time Ser Anal 12(3): 207–224, 1991) (GH) is also considered. In Fotopoulos and Ahn (J Time Ser Anal 24(6): 647–662, 2003), these unit root rank tests were analytically and empirically investigated and compared to the DF test, but with outlier-free processes. Thus, the results provided in this paper complement the studies of the previous works, but in the context of time series with additive outliers. Equivalently to DF and Granger and Hallman (J Time Ser Anal 12(3): 207–224, 1991) unit root tests, the BG test shows to be sensitive to AO contaminations, but with less severity. In practical situations where there would be a suspicion of additive outlier, the general conclusion is that the DF and Granger and Hallman (J Time Ser Anal 12(3): 207–224, 1991) unit root tests should be avoided, however, the BG approach can still be used.

This is a preview of subscription content, access via your institution.

Fig. 1
Fig. 2
Fig. 3

References

  1. Aparicio F, Escribano A, Sipols AE (2006) Range unit-root (rur) tests: robust against nonlinearities, error distributions, structural breaks and outliers. J Time Ser Anal 27(4):545–576

    MathSciNet  Article  MATH  Google Scholar 

  2. Astill S, Harvey D, Taylor AMR (2013) A bootstrap test for additive outliers in non-stationary time series. J Time Ser Anal 34:454–465

    MathSciNet  Article  MATH  Google Scholar 

  3. Billingsley P (1968) Convergence of probability measures. Wiley, New York

    MATH  Google Scholar 

  4. Borovkova S, Burton R, Dehling H (2001) Limit theorems for functionals of mixing processes with applications to \(U\)-statistics and dimension estimation. Trans Am Math Soc 353(11):4261–4318

    MathSciNet  Article  MATH  Google Scholar 

  5. Breitung J (1994) Some simple tests of the moving-average unit root hypothesis. J Time Ser Anal 15(4):351–370

    MathSciNet  Article  MATH  Google Scholar 

  6. Breitung J, Gouriéroux C (1997) Rank tests for unit roots. J Econom 81(1):7–27

    MathSciNet  Article  MATH  Google Scholar 

  7. Breitung J, Hassler U (2002) Inference on the cointegration rank in fractionally integrated processes. J Econom 110(2):167–185

    MathSciNet  Article  MATH  Google Scholar 

  8. Carstensen K (2003) The finite-sample performance of robust unit root tests. Stat Pap 44:469–482

    MathSciNet  Article  MATH  Google Scholar 

  9. Chan W-S (1995) Understanding the effect of time series outliers on sample autocorrelations. Test 4(1):179–186

    MathSciNet  Article  MATH  Google Scholar 

  10. Chen C, Liu L-M (1993) Joint estimation of model parameters and outlier effects in time series. J Am Stat Assoc 88(421):284–297

    MATH  Google Scholar 

  11. Demetrescu M, Kuzin V, Hassler U (2008) Long memory testing in the time domain. Econom Theory 24(01):176–215

    MathSciNet  Article  MATH  Google Scholar 

  12. Denby L, Martin RD (1979) Robust estimation of the first-order autoregressive parameter. J Am Stat Assoc 74(365):140–146

    Article  MATH  Google Scholar 

  13. Dickey DA, Fuller WA (1979) Distribution of the estimators for autoregressive time series with a unit root. J Am Stat Assoc 74(366, part 1):427–431

    MathSciNet  Article  MATH  Google Scholar 

  14. Dickey DA, Fuller WA (1981) Likelihood ratio statistics for autoregressive time series with a unit root. Econometrica 49(4):1057–1072

    MathSciNet  Article  MATH  Google Scholar 

  15. Elliot G, Rothenberg T, Stock J (1996) Efficient tests for an autoregressive unit root. Econometrica 64:813–836

    MathSciNet  Article  MATH  Google Scholar 

  16. Fotopoulos SB, Ahn SK (2003) Rank based Dickey–Fuller test statistics. J Time Ser Anal 24(6):647–662

    MathSciNet  Article  MATH  Google Scholar 

  17. Franco GC, Reisen VA (2007) Bootstrap approaches and confidence intervals for stationary and non-stationary long-range dependence processes. Phys A Stat Mech Appl 375(2):546–562

    Article  Google Scholar 

  18. Franses PH, Haldrup N (1994) The effects of additive outliers on tests for unit roots and cointegration. J Bus Econ Stat 12:471–478

    MathSciNet  Google Scholar 

  19. Granger CWJ, Hallman J (1991) Nonlinear transformations of integrated time series. J Time Ser Anal 12(3):207–224

    MathSciNet  Article  MATH  Google Scholar 

  20. Hallin M, van den Akker R, Werker BJ (2011) A class of simple distribution-free rank-based unit root tests. J Econom 163(2):200–214

    MathSciNet  Article  MATH  Google Scholar 

  21. Hamilton JD (1994) Time series analysis. Princeton University Press, Princeton

    MATH  Google Scholar 

  22. Hassler U, Wolters J (1994) On the power of unit root tests against fractional alternatives. Econ Lett 45(1):1–5

    Article  MATH  Google Scholar 

  23. Kramer W (1998) Fractional integration and the augmented dickey–fuller test. Econ Lett 61(3):269–272

    MathSciNet  Article  MATH  Google Scholar 

  24. Lévy-Leduc C, Boistard H, Moulines E, Taqqu M, Reisen V (2011a) Asymptotic properties of \(U\)-processes under long-range dependence. Ann Stat 39(3):1399–1426

    MathSciNet  Article  MATH  Google Scholar 

  25. Lévy-Leduc C, Boistard H, Moulines E, Taqqu MS, Reisen VA (2011b) Robust estimation of the scale and of the autocovariance function of gaussian short- and long-range dependent processes. J Time Ser Anal 32:135–156

    MathSciNet  Article  MATH  Google Scholar 

  26. Lucas A (1995) An outliers robust unit root test with an application to the extended Nelson-Plosser data. J Econom 66:153–173

    Article  MATH  Google Scholar 

  27. Martin RD, Yohai VJ (1986) Influence functionals for time series. Ann Stat 14(3):781–855 (with discussion)

    MathSciNet  Article  MATH  Google Scholar 

  28. Molinares FF, Reisen VA, Cribari-Neto F (2009) Robust estimation in long-memory processes under additive outliers. J Stat Plan Inference 139(8):2511–2525

    MathSciNet  Article  MATH  Google Scholar 

  29. Palm FC, Smeekes S, Urbain J-P (2008) Bootstrap unit-root tests: comparison and extensions. J Time Ser Anal 29(2):371–401

    MathSciNet  Article  MATH  Google Scholar 

  30. Reisen VA, Molinares FF (2012) Robust estimation in time series with short and long-memry property. Ann Math Inform 39:207–224

    MathSciNet  MATH  Google Scholar 

  31. Robinson PM (1991) Testing for strong serial correlation and dynamic conditional heteroskedasticity in multiple regression. J Econom 47(1):67–84

    MathSciNet  Article  MATH  Google Scholar 

  32. Said SE, Dickey DA (1984) Testing for unit roots in autoregressive-moving average models of unknown order. Biometrika 71(3):599–607

    MathSciNet  Article  MATH  Google Scholar 

  33. Wang G (2011) Unit root testing in the presence of arfima–garch errors. Appl Stoch Models Bus Ind 27:421–433

    MathSciNet  Article  Google Scholar 

  34. Westerlund J (2014) On the asymptotic distribution of the dickey fuller-gls test statistic. Statistics 48(6):1233–1253

    MathSciNet  Article  MATH  Google Scholar 

Download references

Acknowledgments

V. A. Reisen and M. Bourguignon gratefully acknowledge partial financial support from CAPES-CNPq/Brazil and FAPES-ES-Brazil. The authors would like to thank the referee for his valuable suggestions.

Author information

Affiliations

Authors

Corresponding author

Correspondence to V. A. Reisen.

Appendix: Proofs

Appendix: Proofs

Proof of Theorem 2

Let us start by proving (11). Let us first prove that the numerator of (8) is not random but is just a fixed function of T.

$$\begin{aligned}&\sum _{t=2}^T\left\{ \left( r_{T,t}-\frac{T+1}{2}\right) \sum _{j=1}^{t-1}\left( r_{T,j}-\frac{T+1}{2}\right) \right\} \nonumber \\&\quad =\sum _{1\le j<t\le T}\left( r_{T,t}-\frac{T+1}{2}\right) \left( r_{T,j}-\frac{T+1}{2}\right) \nonumber \\&\quad =\frac{\left[ \sum _{j=1}^T \left( r_{T,j}-\frac{T+1}{2}\right) \right] ^2-\sum _{j=1}^T \left( r_{T,j}-\frac{T+1}{2}\right) ^2}{2}\nonumber \\&\quad =-\frac{1}{2}\sum _{j=1}^T r_{T,j}^2+\frac{T+1}{2}\left( \sum _{j=1}^T r_{T,j}\right) -\frac{T}{2}\left( \frac{T+1}{2}\right) ^2\nonumber \\&\quad =-\frac{T(T+1)(T-1)}{24}, \end{aligned}$$
(13)

where we used that \(\sum _{j=1}^T (r_{T,j}-(T+1)/2)=0\) and that \(\sum _{j=1}^T r_{T,j}^2=T(T+1)(2T+1)/6.\)

By (13), studying the asymptotic behavior of (11) amounts to studying the following quantity

$$\begin{aligned} \frac{1}{T^4}\sum _{t=2}^T \left\{ \sum _{j=1}^{t-1}\left( r_{T,j}-\frac{T+1}{2}\right) \right\} ^2= & {} \frac{1}{T^4}\sum _{t=2}^T \left\{ \sum _{j=1}^{t-1}\left[ \left( \sum _{k=1}^T \mathbf {1}_{\{\Delta z_k\le \Delta z_j\}}\right) -\frac{T+1}{2}\right] \right\} ^2\nonumber \\= & {} \frac{1}{T}\sum _{t=2}^T \left\{ \frac{1}{\sqrt{T}}\sum _{j=1}^{t-1}\left( F_T(\zeta _j)-\frac{T+1}{2T}\right) \right\} ^2,\nonumber \\ \end{aligned}$$
(14)

where \(F_T(x)=T^{-1}\sum _{t=1}^T\mathbf {1}_{\{\zeta _t\le x\}}\), where

$$\begin{aligned} \zeta _t=\Delta z_t=\varepsilon _t+\theta (\delta _t-\delta _{t-1}). \end{aligned}$$
(15)

Let us now prove that

$$\begin{aligned} \left\{ \frac{1}{\sqrt{T}}\sum _{i=1}^{[Tu]}\left( F_T(\zeta _i)-\frac{T+1}{2T}\right) ,\quad u\in [0,1]\right\} \mathop {\Longrightarrow }\limits ^{d} \{B(u),\, u\in [0,1]\}, \text { as } T\rightarrow \infty , \end{aligned}$$
(16)

where [x] denotes the integer part of x, \( \{B(u),\, u\in [0,1]\}\) denotes the Brownian bridge and \(\mathop {\Longrightarrow }\limits ^{d}\) denotes here the weak convergence in the space of cadlag functions of [0, 1] denoted \(\mathcal {D}([0,1])\) and equipped with the topology of uniform convergence. Splitting \(\sum _{j=1}^T\) into \(\sum _{j=1}^{[Tu]}\) and \(\sum _{j=[Tu]+1}^T\), we get

$$\begin{aligned} \frac{1}{\sqrt{T}}\sum _{i=1}^{[Tu]}\left( F_T(\zeta _i)-\frac{T+1}{2T}\right)= & {} \frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=1}^T\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{T+1}{2T}\right) \nonumber \\= & {} \frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\left\{ \sum _{j=1}^T\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \right\} -\frac{[Tu]}{2T^{3/2}}\nonumber \\= & {} \frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\left\{ \sum _{j=1}^{[Tu]}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \right\} \nonumber \\&+\,\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\left\{ \sum _{j=[Tu]+1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \right\} -\frac{[Tu]}{2T^{3/2}}.\nonumber \\ \end{aligned}$$
(17)

Let \(f(x,y)=\mathbf {1}_{\{x\le y\}}-1/2\). Since \(f(y,x)=-f(x,y)\), when \(x\ne y\), we get that the first term in the r.h.s of (17) is equal to

$$\begin{aligned} \frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\left\{ \sum _{j=1}^{[Tu]}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \right\} =\frac{1}{T^{3/2}} \sum _{i=1}^{[Tu]}\left( \mathbf {1}_{\{\zeta _i\le \zeta _i\}}-\frac{1}{2}\right) =\frac{[Tu]}{2T^{3/2}}. \end{aligned}$$
(18)

Thus,

$$\begin{aligned} \frac{1}{\sqrt{T}}\sum _{i=1}^{[Tu]}\left( F_T(\zeta _i)-\frac{T+1}{2T}\right) =\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\left\{ \sum _{j=[Tu]+1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \right\} . \end{aligned}$$
(19)

Let \(h(x,y)=\mathbf {1}_{\{x\le y\}}\). By using the Hoeffding’s decomposition, we get that

$$\begin{aligned}&\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( h(\zeta _j,\zeta _i)-\frac{1}{2}\right) \nonumber \\&\quad =\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( F(\zeta _i)-\frac{1}{2}\right) -\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( F(\zeta _j)-\frac{1}{2}\right) \nonumber \\&\qquad +\,\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( h(\zeta _j,\zeta _i)-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) , \end{aligned}$$
(20)

F denoting the c.d.f of \((\zeta _t)\). Observe that since \(\varepsilon _t\) has a continuous c.d.f it is also the case of the c.d.f of \(\zeta _t\).

Let us now study the behavior of the first two terms in the r.h.s of (20):

$$\begin{aligned} \frac{T-[Tu]}{T^{3/2}}\sum _{i=1}^{[Tu]}\left( F(\zeta _i)-\frac{1}{2}\right) -\frac{[Tu]}{T^{3/2}}\sum _{j=[Tu]+1}^{T}\left( F(\zeta _j)-\frac{1}{2}\right) =X_{T,u}+Y_{T,u}. \end{aligned}$$

Observe first that \((\zeta _i)\) is a strictly stationary process since it is defined as the sum of two strictly stationary processes. It is also a 1-dependent process in the sense of Example 1 p. 167 of Billingsley (1968) and \((F(\zeta _i))\) has the same properties. By using Theorem 20.1 of Billingsley (1968), we get that, as T tends to infinity, \(\{X_{T,u}\}\mathop {\Longrightarrow }\limits ^{d}\{(1-u) W(u)\}\), and that \(\{Y_{T,u}\}\mathop {\Longrightarrow }\limits ^{d}\{u(W(1)-W(u))\}\), where \(\{W(u)\}\) denotes the Wiener process. Since the process \((X_{T,u},Y_{T,u})\) is tight and since for fixed u and s, \(\text {Cov}(X_{T,u},Y_{T,s})\rightarrow \text {Cov}((1-u) W(u),s(W(1)-W(s)))\), as \(T\rightarrow \infty \), \(\{(X_{T,u},Y_{T,u})\}\mathop {\Longrightarrow }\limits ^{d}\{((1-u) W(u),u(W(1)-W(u))\}\).

We deduce from this and Lemma 3 that

$$\begin{aligned}&\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( h(\zeta _j,\zeta _i)-\frac{1}{2}\right) \mathop {\longrightarrow }\limits ^{d} (1-u)W(u)-u(W(1)-W(u))\nonumber \\&\quad =W(u)-uW(1), \end{aligned}$$
(21)

which with (19) gives (16).

Let \(w_i=F_T(\zeta _i)-(T+1)/(2T).\) Using similar arguments as those used in (Hamilton 1994, p. 483)

$$\begin{aligned}&\frac{1}{T}\sum _{t=2}^T \left\{ \frac{1}{\sqrt{T}}\sum _{j=1}^{t-1}\left( F_T(\zeta _j)-\frac{T+1}{2T}\right) \right\} ^2\\&\quad =\frac{1}{T} \left[ \left( \frac{w_1}{\sqrt{T}}\right) ^2+\left( \frac{w_1+w_2}{\sqrt{T}}\right) ^2+\cdots +\left( \frac{w_1+\cdots +w_{T-1}}{\sqrt{T}}\right) ^2\right] \\&\quad =\int _0^1\left( \frac{1}{\sqrt{T}}\sum _{i=1}^{[Tu]}w_i\right) ^2\mathrm {d}t \mathop {\longrightarrow }\limits ^{d} \int _0^1 B(u)^2\mathrm {d}u, \end{aligned}$$

by the continuous mapping theorem and (16), which concludes the proof of (11).

Lemma 3

Under the assumptions of Theorem 2,

$$\begin{aligned}&\sup _{u\in [0,1]}\left| \frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=[Tu]+1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) \right| =\sup _{u\in [0,1]} |Z_T(u)|\nonumber \\&\qquad =o_p(1), \text { as } T\rightarrow \infty . \end{aligned}$$
(22)

Proof of Lemma 3

Observe that

$$\begin{aligned} Z_T(u)=\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) -\frac{[Tu]}{2T^{3/2}}. \end{aligned}$$

Thus it is enough to prove (22) when \(Z_T(u)\) is replaced by

$$\begin{aligned} R_T(u)=\frac{1}{T^{3/2}}\sum _{i=1}^{[Tu]}\sum _{j=1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) . \end{aligned}$$

We want to apply Lemma 5.2 of Borovkova et al. (2001) to \(\{R_T(u),\; t\in [0,1]\}\). Let us first prove that for s and u such that \(0\le s\le u <s+\delta \le 1\),

$$\begin{aligned}&R_T(u)-R_T(s)\\&\quad \le |R_T(s+\delta )-R_T(s)| + |W_T(s+\delta )-W_T(s)| + 2 \frac{[T(s+\delta )]-[Ts]}{\sqrt{T}}, \end{aligned}$$

where

$$\begin{aligned} W_T(u)=\frac{T-[Tu]}{T^{3/2}}\sum _{i=1}^{[Tu]}\left( F(\zeta _i)-\frac{1}{2}\right) -\frac{[Tu]}{T^{3/2}}\sum _{j=[Tu]+1}^{T}\left( F(\zeta _j)-\frac{1}{2}\right) . \end{aligned}$$
(23)

Observe that

$$\begin{aligned} R_T(u)-R_T(s)=\frac{1}{T^{3/2}}\sum _{i=[Ts]+1}^{[Tu]} \sum _{j=1}^{T}\left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) . \end{aligned}$$
(24)

Thus,

$$\begin{aligned}&(R_T(u)-R_T(s))-(R_T(s+\delta )-R_T(s))\\&\quad =-\frac{1}{T^{3/2}}\sum _{i=[Tu]+1}^{[T(s+\delta )]}\sum _{j=1}^T \left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-\frac{1}{2}\right) \\&\quad =-\frac{1}{T^{3/2}}\sum _{i=[Tu]+1}^{[T(s+\delta )]}\sum _{j=1}^T \left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) \\&\qquad +\,\frac{T}{T^{3/2}}\sum _{i=[Tu]+1}^{[T(s+\delta )]} \left( F(\zeta _i)-\frac{1}{2}\right) +\frac{[Tu]-[T(s+\delta )]}{T^{3/2}} \sum _{j=1}^T\left( F(\zeta _j)-\frac{1}{2}\right) . \end{aligned}$$

Using (23),

$$\begin{aligned}&W_T(s+\delta )-W_T(s)\\&\quad =\frac{1}{\sqrt{T}}\sum _{i=[Ts]+1}^{[T(s+\delta )]}\left( F(\zeta _i)-\frac{1}{2}\right) +\frac{[Ts]-[T(s+\delta )]}{T^{3/2}}\sum _{j=1}^T\left( F(\zeta _j)-\frac{1}{2}\right) , \end{aligned}$$

and thus, we get that

$$\begin{aligned}&(R_T(u)-R_T(s))-(R_T(s+\delta )-R_T(s))-(W_T(s+\delta )-W_T(s))\\&\quad =-\frac{1}{T^{3/2}}\sum _{i=[Tu]+1}^{[T(s+\delta )]}\sum _{j=1}^T \left( \mathbf {1}_{\{\zeta _j\le \zeta _i\}}-\frac{1}{2}\right) -\frac{1}{\sqrt{T}}\sum _{i=[Ts]+1}^{[Tu]}\left( F(\zeta _i)-\frac{1}{2}\right) \\&\qquad +\,\frac{[Tu]-[Ts]}{T^{3/2}}\sum _{j=1}^T\left( F(\zeta _j)-\frac{1}{2}\right) \le \frac{3}{2}\frac{[T(s+\delta )]-[Ts]}{\sqrt{T}}. \end{aligned}$$

Since we can follow the same line of reasoning for \(R_T(s)-R_T(u)\), we get Condition (5.10) of Lemma 5.2 in Borovkova et al. (2001) with \(\alpha =1/2\).

Let us now check Condition (5.9) of Lemma 5.2 in Borovkova et al. (2001). Observe that for \(0\le s\le u\le 1\),

$$\begin{aligned} W_T(u)-W_T(s)= & {} \frac{T-([Tu]-[Ts])}{T^{3/2}}\sum _{i=[Ts]+1}^{[Tu]}\left( F(\zeta _i)-\frac{1}{2}\right) \\&+\,\frac{[Ts]-[Tu]}{T^{3/2}}\left\{ \sum _{i=1}^{[Ts]}\left( F(\zeta _i)-\frac{1}{2}\right) + \sum _{i=[Tu]+1}^{T}\left( F(\zeta _i)-\frac{1}{2}\right) \right\} . \end{aligned}$$

Thus, for some positive constant \(C_1\)

$$\begin{aligned} \mathbb {E}[(W_T(u)-W_T(s))^4]\le & {} C_1\frac{(T-([Tu]-[Ts]))^4}{T^6} \mathbb {E}\left[ \left\{ \sum _{i=[Ts]+1}^{[Tu]}\left( F(\zeta _i)-\frac{1}{2}\right) \right\} ^4\right] \\&+\,C_1\frac{([Tu]-[Ts])^4}{T^{6}}\mathbb {E}\left[ \left\{ \sum _{i=1}^{[Ts]}\left( F(\zeta _i)-\frac{1}{2}\right) \right\} ^4\right] \\&+\,C_1\frac{([Tu]-[Ts])^4}{T^{6}}\mathbb {E}\left[ \left\{ \sum _{i=[Tu]+1}^{T}\left( F(\zeta _i)-\frac{1}{2}\right) \right\} ^4\right] . \end{aligned}$$

Using that \((\zeta _i)\) is a 1-dependent process and that \(\mathbb {E}[(F(\zeta _i)-1/2)]=0\), \(|F(\zeta _i)-1/2|\le 1/2\) for all \(i\ge 1\), there exist positive constants \(C_2\) and \(C_3\) such that

$$\begin{aligned}&\mathbb {E}[(W_T(u)-W_T(s))^4]\\&\quad \le C_2\frac{(T-([Tu]-[Ts]))^4}{T^6} \left\{ ([Tu]-[Ts])+([Tu]-[Ts])^2\right\} \\&\qquad +\,C_2\frac{([Tu]-[Ts])^4}{ T^{6}} \left\{ [Ts]+[Ts]^2+(T-[Tu])+(T-[Tu])^2\right\} \\&\quad \le C_3 \left\{ \frac{([Tu]-[Ts])^2}{T^{2}}+\frac{([Tu]-[Ts])}{T^{2}}\right\} , \end{aligned}$$

which is Condition (5.10) of Lemma 5.2 in Borovkova et al. (2001) with \(h=1\), \(g(t)=t\) and \(r=4\).

Let us now check Condition (5.8) of Lemma 5.2 in Borovkova et al. (2001). Using (24), we get that for \(0\le s\le u\le 1\),

$$\begin{aligned}&\mathbb {E}[(R_T(u)-R_T(s))^2]\\&\quad =\mathbb {E}\left[ \left\{ \frac{1}{T^{3/2}}\sum _{i=[Ts]+1}^{[Tu]} \sum _{j=1}^{[Ts]} A_{i,j}+\frac{1}{T^{3/2}}\sum _{i=[Ts]+1}^{[Tu]}\sum _{j=[Tu]+1}^{T} A_{i,j} +\frac{[Tu]-[Ts]}{2T^{3/2}}\right\} ^2\right] \\&\quad \le \frac{3}{T^{3}} \mathbb {E}\left[ \left\{ \sum _{i=[Ts]+1}^{[Tu]} \sum _{j=1}^{[Ts]} A_{i,j}\right\} ^2\right] +\frac{3}{T^{3}} \mathbb {E}\left[ \left\{ \sum _{i=[Ts]+1}^{[Tu]}\sum _{j=[Tu]+1}^{T} A_{i,j}\right\} ^2\right] \\&\qquad +\,\frac{3([Tu]-[Ts])^2}{2T^{3}}, \end{aligned}$$

where \(A_{i,j}=\mathbf {1}_{\{\zeta _j\le \zeta _i\}}-F(\zeta _i)+F(\zeta _j)-1/2\). Using that \((\zeta _i)\) is a 1-dependent process, that \(\mathbb {E}(A_{i,j})=0\) for all \(i\ne j\) and that \(\mathbb {E}(A_{i,j}A_{k,\ell })=0\) as soon as the distances between the different indices \(i,j,k,\ell \) is larger than 1, there exist positive constants \(C_4\), \(C_5\) and \(C_6\) such that

$$\begin{aligned} \mathbb {E}[(R_T(u)-R_T(s))^2]\le & {} C_4 \frac{([Tu]-[Ts])[Ts]}{T^{3}}+ C_4\frac{([Tu]-[Ts])(T-[Tu])}{T^{3}}\\&+\,C_5\frac{([Tu]-[Ts])^2}{T^{3}} \le C_6\frac{|u-s|}{T}\le C_6\frac{|u-s|^{1-\nu }}{T}, \end{aligned}$$

for some positive \(\nu \) which gives Condition (5.8) of Lemma 5.2 in Borovkova et al. (2001) with \(\beta =1\) and \(\gamma =1-\nu \) and thus concludes the proof of Lemma 3. \(\square \)

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Reisen, V.A., Lévy-Leduc, C., Bourguignon, M. et al. Robust Dickey–Fuller tests based on ranks for time series with additive outliers. Metrika 80, 115–131 (2017). https://doi.org/10.1007/s00184-016-0594-8

Download citation

Keywords

  • Time series
  • Robust tests
  • Ranks
  • Outliers
  • Unit root